The Effect of Trust, Spirituality, and Interpersonal Communication on Organizational Citizenship Behaviour Certified Lecturer - Mansyur, Mansyur; Akib, Akib; Syahrul, Syahrul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This article analyses the effect of Belief, Spirituality, and Interpersonal Communication on organizational citizenship behaviour (OCB). The research was conducted on seventy-two certified lecturers using path analysis. The results of the study show that there are direct and indirect effects of; 1) trust on the organizational citizenship behaviour of certified lecturers, 2) spirituality on the organizational citizenship behaviour of certified lecturers, 3) interpersonal communication on the organizational citizenship behaviour of certified lecturers; 4) belief in spirituality; 5) trust in interpersonal communication; 6) trust in organizational citizenship behaviour of certified lecturers through spirituality; 7) trust in organizational citizenship behaviour of certified lecturers through interpersonal communication. The results of this study confirm that high levels of trust, spirituality, and interpersonal communication influence any change in the organizational citizenship behaviour of certified lecturers. Therefore, these three variables must be considered in creating and improving the organizational citizenship behaviour of certified lecturers.